2011
DOI: 10.1088/0004-637x/734/1/11
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Star Clusters in the Interacting Antennae Galaxies

Abstract: We reexamine the age distribution of star clusters in the Antennae in the context of N-body+hydrodynamical simulations of these interacting galaxies. All of the simulations that account for the observed morphology and other properties of the Antennae have star formation rates that vary relatively slowly with time, by factors of only 1.3 − 2.5 in the past 10 8 yr. In contrast, the observed age distribution of the clusters declines approximately as a power law, dN/dτ ∝ τ γ with γ = −1.0, for ages 10 6 yr τ 10 9 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Linden et al (2010) show in their Figure 1 that in solar metallicity systems like the Antennae, bright (L X > 10 36 erg s −1 ) HMXBs turn on suddenly at ages of approximately 4 Myr, with a production rate that is sharply peaked between 4 and 6 Myr and dropping off thereafter. These ages are quite similar to those listed in Table 1 for many coincident clusters, and are probably not due to a peak in the star formation rate 4-6 Myr ago, since (1) dynamical simulations which reproduce the observed morphology of the merging Antennae do not find such a peak in the star formation rate (see, e.g., Karl et al 2011), and (2) it would be impossible to have such a well-timed burst over the entire field of the Antennae since the communication time is ∼10 9 yr for a signal traveling at the typical random velocity of the interstellar medium of ≈10 km s −1 (e.g., Fall et al 2009;Whitmore et al 2007). Hence, our age analysis is consistent with predictions for the production timescale of HMXBs in high-metallicity galaxies.…”
Section: The Nature Of Hmxbs Associated With Star Clusters In the Antsupporting
confidence: 80%
“…Linden et al (2010) show in their Figure 1 that in solar metallicity systems like the Antennae, bright (L X > 10 36 erg s −1 ) HMXBs turn on suddenly at ages of approximately 4 Myr, with a production rate that is sharply peaked between 4 and 6 Myr and dropping off thereafter. These ages are quite similar to those listed in Table 1 for many coincident clusters, and are probably not due to a peak in the star formation rate 4-6 Myr ago, since (1) dynamical simulations which reproduce the observed morphology of the merging Antennae do not find such a peak in the star formation rate (see, e.g., Karl et al 2011), and (2) it would be impossible to have such a well-timed burst over the entire field of the Antennae since the communication time is ∼10 9 yr for a signal traveling at the typical random velocity of the interstellar medium of ≈10 km s −1 (e.g., Fall et al 2009;Whitmore et al 2007). Hence, our age analysis is consistent with predictions for the production timescale of HMXBs in high-metallicity galaxies.…”
Section: The Nature Of Hmxbs Associated With Star Clusters In the Antsupporting
confidence: 80%
“…The best match with observations being reached at t = 152 Myr, we note that the SFR has declined and increased again before reaching the present day, by a factor up to ∼ 3 during the last 100 Myr, which contradicts the assumption of a constant SFR made by Karl et al (2011) to interpret the observed age distribution of clusters in the Antennae. A longer time-lapse between the pericenter passages would allow the SFR to reach a relatively constant value after the first starburst and would thus be more consistent with the assumption of Karl et al (2011). In our simulation, the SFR averaged over the last 100 Myr is higher than the presentday value.…”
Section: Star Formation Historymentioning
confidence: 40%
“…Unfortunately, to our knowledge, there is no published SFH for the merging, starbursting NGC 3256 system, either from direct observations or from high quality simulations. If the SFH of NGC 3256 has been constant to within a factor of a few over this timescale, as suggested by some simulations for the starbursting Antennae galaxies (Karl, Fall, & Naab 2011), as well as observational works on interacting galaxies (e.g., Knapen, Cisternas, & Querejeta 2015 and references therein), then the clusters in NGC 3256 would also have a disruption history similar to that found in these more quiescent galaxies.…”
Section: Age Distributionmentioning
confidence: 74%